Comparison of the factors that influence the pattern of procurement and usage of antithrombotic drugs - Mohamed Mansor Manan; Aswani Yanti Baharudin; Qi Ying Lean; Jagjit Singh Dhaliwal; Sachinjeet Kaur Sodhi Dhaliwal; Muhammad Junaid Farrukh; Ching Siang Tan; Long Chiau Ming (Progress in Microbes and Molecular Biology)
Antithrombotics are used for many indications in prophylaxis and therapeutic treatment. It is often associated with a higher risk of adverse effects; hence a drug utilization evaluation is essential. The main aim was to describe the utilization of antithrombotic drugs. The specific objectives are to compare the pattern of procurement and usage of antithrombotic drugs, estimate the Defined Daily Dose (DDD), and to compare the usage of antithrombotic drugs with the WHO recommended standard. This was a retrospective study evaluating the utilization of antithrombotics at a public tertiary care hospital in the urban city of Klang Valley, Malaysia. A defined daily dose (DDD) per 1000 inhabitants/day was calculated to estimate patients with thromboembolic disorders receiving standard treatment on a daily basis. Expenditures on all antithrombotic drugs were also assessed. The DDD was examined for correlation with gender, race, and age group. Malaysian Clinical Practice Guideline on the Prevention and Treatment of Venous Thromboembolism was used as a tool to evaluate the quality of prescribing. During the study period, among anticoagulants prescribed, warfarin was the most commonly utilized for treatment and prophylaxis in various disciplines, with 1.82 DDD. Enoxaparin was the second most utilized anticoagulant, with 1.05 DDD, followed by tinzaparin, with 0.39 DDD. For antiplatelet drugs, acetylsalicylic acid was the most utilized antiplatelet with 8.5 DDD followed by clopidogrel (1.42 DDD) and ticlopidine (0.16 DDD). The utilization pattern for all the antithrombotic drugs was in accordance with the WHO DDD guidelines. The pattern of antithrombotic drug procured was based on the demand for the drug supplies. Age, gender, and race were determinant factors that influenced the choice of antithrombotic drugs and further affected the antithrombotic drug utilization pattern. Still, additional information regarding patient’s status and concomitant disease condition is needed to establish the impact of utilization of antithrombotics fully. DDD analysis is an excellent practice to be conducted at planned intervals. It is a tool to update the changing or even new pattern of drug usage, which will assist in the justification of rational use of drugs. The mean difference in terms of DDDs of the studied antithrombotic drugs impacts patient demographic characteristics, smoking history, presence of atherosclerotic diseases and peripheral artery diseases, comorbidity, patient compliance, and bleeding history. It is useful to evaluate trends and expenditures, which will ultimately avoid untoward adverse effects and unnecessary costs.